Corrigendum: Status Terkini Penyakit Tristeza Pada Tanaman Jeruk di Sulawesi Tenggara. : Corrigendum: Status Terkini Penyakit Tristeza Pada Tanaman Jeruk di Sulawesi Tenggara. - Editors Jurnal Fitopatologi Indonesia (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
Corrigendum: Taufik M, Nurulita S, Yusuf DN, Miftahkuhrohmah, Botek M, Gusnawaty HS, Syarni E. 2025. Status Terkini Penyakit Tristeza Pada Tanaman Jeruk di Sulawesi Tenggara. Jurnal Fitopatologi Indonesia. 21(1):28-37. DOI: https://doi.org/10.14692/jfi.21.1.28-37.In the original version of this article, the affiliation of the author Miftahkuhrohmah was incorrectly stated as: “National Research and Innovation Agency, Jalan Raya Bogor KM 46, Bogor 16915”. The correct affiliation is: “Research Center for Estate Crops, National Research and Innovation Agency, Jalan Raya Jakarta–Bogor km 46, Cibinong, Bogor, West Java, 16911”. This correction does not affect the substance, data, or conclusions of the article. The correction has been made in the online version and the PDF version of the article.